2016
DOI: 10.1002/pon.4287
|View full text |Cite
|
Sign up to set email alerts
|

What do people fear about cancer? A systematic review and meta‐synthesis of cancer fears in the general population

Abstract: BackgroundCancer has long inspired fear, but the effect of fear is not well understood; it seems both to facilitate and to deter early diagnosis behaviours. To elucidate fear's behavioural effects, we systematically reviewed and synthesised qualitative literature to explore what people fear about cancer.MethodsWe searched Medline, Embase, PsycInfo, Web of Science, AnthroSource, and Anthrobase for studies on cancer fear in breast, cervical, and colorectal cancer screening and analysed 102 studies from 26 countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 60 publications
5
88
2
5
Order By: Relevance
“…The psychological sphere is one of the most important because, apart from the ill person, also people who are the closest experience various types of negative emotions, such as fear, anger, the feeling of threat, helplessness and uncertainty [6,7]. Some researchers emphasize the importance of the patient's attitude towards the disease and the skills of coping with emotions resulting from the health situation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The psychological sphere is one of the most important because, apart from the ill person, also people who are the closest experience various types of negative emotions, such as fear, anger, the feeling of threat, helplessness and uncertainty [6,7]. Some researchers emphasize the importance of the patient's attitude towards the disease and the skills of coping with emotions resulting from the health situation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that may make people not seek care in health facilities are fears related to a cancer diagnosis. A systematic review of 102 studies from 26 countries showed that people fear a cancer diagnosis because cancer is considered a vicious, unpredictable enemy that attacks unannounced, and often leads to death of the victims . While fear about getting cancer may prompt screening for cancers, fear about cancer treatment may lead to delayed help‐seeking to avoid being diagnosed with a cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Con todo, cuando la mujer no presenta síntomas de la enfermedad o no comprenden la importancia de realizar el seguimiento, la no adhesión al examen de rutina es más evidente. Tal comportamiento es significativo del aumento de la incidencia y mortalidad de mujeres diagnosticadas tardíamente (14,15) . Hay relato de que de un cuarto a un tercio de la población femenina no siente la necesidad de realizar el examen citopatológico debido a la ausencia de síntomas (16) .…”
Section: Discussionunclassified